How transportation infrastructure affects firm Productivity?Evidence from China - Ming Xu; Yuan Feng (China Economic Quarterly International, 2022)
The national trunk highway system (NTHS), consisting of five vertical and seven horizontal national trunk highways, is taken as a natural experiment to study the impact of transportation infrastructure on firm productivity. It is found that the NTHS has led to the agglomeration of production resources of county-level enterprises along the system to large cities, and the degree of agglomeration has industry-level heterogeneity. Although the NTHS has promoted the division of labor among county-level enterprises, it is difficult for these enterprises to compete with those in big cities and share efficiency and economic benefits from the deepening of the division of labor.